Suatu Tinjauan Theologis Mengenai Misteri Akan Pengharapan Kedatangan Yesus Kembali Yang Tidak Kunjung Tiba? - Rendi Risky Laowo; Aprianus Ledrik Moimau (LPPM - STT Kadesi Bogor, 2024)
Eschatological teaching in Christian theology will of course often intersect with the hope of Christ’s return. As written in the Book of Acts and other books in teh New Testament as Well as the entire Holy Bible. The return of Jesus Christ will not be an ordinary presensce. Just like His first coming in the incarnation of Jesus Christ. He came to the world to fulfill Gd’s promise in His work to save humans from sin. Likewise, the return of Christ will certainly present a very great work. Jesus Christ will come again no longer as a helper for sinners but as judge of the world. Therefore, it is not surprising why eschatological teachings are teachings that have significance in the Christian faith and also for axisting religions. So taht it gives meaning and hope for all sinful humans to immediately prepare themselves to welcome the return of Christ as judge of the world. However, the problem for everyone today is that no one knows when the day of Christ’s return will come. In fact, several verses in the Holy Bible say taht Jesus himself did not know, only the Father knew. This is a very serious problem in Christian theology. That is why all the time there have been theologians, clergy, academics, and so on trying to find answers to these problems. Likewise, this article will discuss this issue using a Systematic Theology approach. In the Research Methods section, we will explain in detail what is meant by research methods and methodologically what research method approach will be used. In This case, the discussion regarding the Parousia from a theological perspective will be researched using qualitative research. Furthermore, here the term Method 2 Samuel Benyamin Hakh, New Testament History and Its Theological Principles, (Bandung: Bina Media Information, 2010) 239-241 come from Greek which means following in the footsteps or investigating and researching where this word comes from the word methodos. So it will support the resolution of the problems discussed in this article.